1995
DOI: 10.1021/bi00016a003
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional structure, catalytic properties, and evolution of a sigma class glutathione transferase from squid, a progenitor of the lens S-crystallins of cephalopods

Abstract: The glutathione transferase from squid digestive gland is unique in its very high catalytic activity toward 1-chloro-2,4-dinitrobenzene and in its ancestral relationship to the genes encoding the S-crystallins of the lens of cephalopod eye. The three-dimensional structure of this glutathione transferase in complex with the product 1-(S-glutathionyl)-2,4-dinitrobenzene (GSDNB) has been solved by multiple isomorphous replacement techniques at a resolution of 2.4 A. Like the cytosolic enzymes from vertebrates, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
225
1
2

Year Published

1996
1996
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(240 citation statements)
references
References 36 publications
12
225
1
2
Order By: Relevance
“…Both the wild-type pi class GST and an enzymatically inactivate mutant were shown to inhibit activation of the nuclear transcriptional activating protein jun by jun kinase (JNK), with the GST's C-terminal residues (194 to 201) being implicated as important for this inhibitory activity. The S-crystallins of cephalopods, which perform a refractive function in the eye lens, have evolved from a sigma class GST (48,49).…”
Section: Resultsmentioning
confidence: 99%
“…Both the wild-type pi class GST and an enzymatically inactivate mutant were shown to inhibit activation of the nuclear transcriptional activating protein jun by jun kinase (JNK), with the GST's C-terminal residues (194 to 201) being implicated as important for this inhibitory activity. The S-crystallins of cephalopods, which perform a refractive function in the eye lens, have evolved from a sigma class GST (48,49).…”
Section: Resultsmentioning
confidence: 99%
“…structures of representatives of the a class (Sinning et al, 1993), p class Raghunathan et al, 1994), T class (Reinemer et al, 1991(Reinemer et al, , 1992Garcia-Saez et al, 1994), and u class (Ji et al, 1995) have been determined from X-ray crystallography. The tyrosine residue near the N-terminal end of the enzyme is conserved in all known mammalian cytosolic glutathione S-transferases and is considered to be essential for catalysis (Wilce & Parker, 1994).…”
Section: -1mentioning
confidence: 99%
“…The catalytic diversity of mammalian cytosolic GSTs, which can exist as homo-or heterodimers, arises in part from the existence of at least eight distinct classes (named Alpha, Kappa, Mu, Omega, Pi, Sigma, Theta, and Zeta) (1,4). The glutathione-binding site (G-site) and the catalytic mechanism of these enzymes have been the targets of many investigations involving chemical modification (5)(6)(7)(8), site-directed mutagenesis (9 -14), and x-ray crystallographic analysis (15)(16)(17)(18)(19)(20)(21). On the contrary, the electrophilic substrate-binding site (H-site) of GSTs is more complex and is class-specific.…”
mentioning
confidence: 99%
“…On the contrary, the electrophilic substrate-binding site (H-site) of GSTs is more complex and is class-specific. Crystallographic studies have shown that the H-site is quite dissimilar among different classes of GSTs (15)(16)(17)(18)(19)(20)(21). For example, in GST M1-1, the H-site is a hydrophobic cavity, whereas in GST P1-1 (15), the H-site is half-hydrophobic and half-hydrophilic with functionally important water molecules (16).…”
mentioning
confidence: 99%